Senpai is an otokonoko : my crossdressing classmate. 1 - Pomu (Illustrator) (Kodansha USA Publishing, LLC, 2025)
First-year high school student Saki is head-over-heels for the older Makoto. After all, this senpai is tall, beautiful, and oh-so-cool... Who wouldn't fall for a girl like her? The bright and bubbly Saki doesn't hesitate to confess her feelings. But Makoto turns her down, because Makoto isn't a girl, but rather a cross-dressing boy! While Saki's determined to win him over regardless, she has a competition for the heart of her daring classmate in the form of Hanaoka's devoted best friend...